Surgical technique for short lateral segment unilateral cleft lip repair - Rossell Perry, Percy (2010)
Background: The anatomy of the cleft lip is different for each patient and many authors have been described modifications of traditional techniques in order to obtain a more individual design and better results. Millards technique is probably the most common surgical technique used by surgeons around the world, however there are some short-comings to repair more severe forms of unilateral cleft. In that way, we have developed a new technique which corrects the medíal and lateral lip segments deficiency in unilateral cleft lip. This technique is based on a double rotation advancement concept placing the scars over the natural lines between the aesthetic subunits of the upper lip. Material and method: This is a retrospective study. This article presents a new technique for unilateral cleft lip repair used by us in 250 patients. In order to evaluate the efficacy of this technique we use a randomized sample of 72 patients. This technique is based in the double rotation advancement concept which let us the lengthening of both (medíal and lateral) lip segments of the unilateral cleft lip. All the incisions are placed on natural landmarks, between the aesthetic subunits of the upper lip. The evaluation of this technique was made in relation with the number of bad results in a period of time longer than one year through the physical exam and postoperatory pictures. Results: Since 2008 to 2010, this technique has been used in 250 unilateral clef lip repairs. We obtain a good functional and aesthetic result of the nose and upper lip with this technique. We obtained 7 / 72 (9.72 %) of bad results (surgeries with secondary lip revision). Conclusions: A new technique for severe forms of unilateral cleft lip repair is described here. This is a technique which let us obtain good aesthetic and functional results on upper lip and nose reconstruction of unilateral cleft lip cases, making an elongation of both (medíal and lateral) lip segments.